Effects of global Ripk2 genetic deficiency in aged mice following experimental ischemic stroke - John Aaron Howell; Jonathan Larochelle; Rachel E. Gunraj; Sofia M. Stansbury; Lei Liu; Changjun Yang; Eduardo Candelario-Jalil (Aging Brain)
Besides the loss of blood and oxygen reaching the ischemic tissue, many secondary effects of ischemic stroke can cause additional tissue damage, including inflammation, oxidative stress, and proteomic disturbances. Receptor-interacting serine/threonine kinase 2 (RIPK2) is an important mediator in the post-stroke inflammatory cascade that responds to signals and molecular patterns released by dead or dying cells in the ischemic area. We hypothesize that RIPK2 signaling worsens injury and neurological recovery post-stroke and that global deletion of Ripk2 is protective following ischemic stroke in aged mice. Aged (18–24 months) male mice were subjected to permanent middle cerebral artery occlusion (pMCAO). Vertical grid, weight grip, and open field were conducted at baseline and on days 1, 2, 3, 8, 15, and 22 post-stroke. Cognitive tests (novel object recognition and Y-maze) were performed at baseline and day 28 post-stroke. Infarct size was measured using cresyl violet staining, and reactive gliosis was measured using Iba1 and GFAP staining at day 28 post-stroke. Global deletion of Ripk2 (Ripk2-/-) in aged mice resulted in smaller infarct volume and improved performance on vertical grid and weight grip tests compared to aged wildtype (WT) mice. Additionally, aged Ripk2-/- mice had less Iba1 staining in the ipsilateral cortex than the aged WT control mice. This study further elucidates the role of RIPK2 signaling in the ischemic cascade and expands our knowledge of RIPK2 in stroke to aged mice. These results support the hypothesis that RIPK2 signaling worsens injury post-stroke and may be an attractive candidate for therapeutic intervention.